2015
DOI: 10.1007/s00406-015-0590-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological background of negative symptoms

Abstract: Studies investigating neurobiological bases of negative symptoms of schizophrenia failed to provide consistent findings, possibly due to the heterogeneity of this psychopathological construct. We tried to review the findings published to date investigating neurobiological abnormalities after reducing the heterogeneity of the negative symptoms construct. The literature in electronic databases as well as citations and major articles are reviewed with respect to the phenomenology, pathology, genetics and neurobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 226 publications
3
71
0
2
Order By: Relevance
“…Our results add to existing PET/SPECT (de Haan et al, 2000; Heinz et al, 1998; Lataster et al, 2011; Martinot et al, 1994; Pickar et al, 1996; Uchida et al, 2009; Voruganti et al, 2001; Voruganti and Awad, 2006) and fMRI (Dowd and Barch, 2010, 2012; Galderisi et al, 2015; Goghari et al, 2010; Juckel et al, 2006a; Simon et al, 2010; Strauss et al, 2014; Waltz et al, 2009; Waltz et al, 2010) evidence that negative symptom severity relates to altered subcortical DA signaling and striatal reactivity, respectively. Our findings are also in line with those of other studies in which genetic profile scores reflecting high DA signaling capacity relate to increased brain responsivity to reward (Nikolova et al, 2011; Stice et al, 2012) and lower depressive symptom severity (Pearson-Fuhrhop et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…Our results add to existing PET/SPECT (de Haan et al, 2000; Heinz et al, 1998; Lataster et al, 2011; Martinot et al, 1994; Pickar et al, 1996; Uchida et al, 2009; Voruganti et al, 2001; Voruganti and Awad, 2006) and fMRI (Dowd and Barch, 2010, 2012; Galderisi et al, 2015; Goghari et al, 2010; Juckel et al, 2006a; Simon et al, 2010; Strauss et al, 2014; Waltz et al, 2009; Waltz et al, 2010) evidence that negative symptom severity relates to altered subcortical DA signaling and striatal reactivity, respectively. Our findings are also in line with those of other studies in which genetic profile scores reflecting high DA signaling capacity relate to increased brain responsivity to reward (Nikolova et al, 2011; Stice et al, 2012) and lower depressive symptom severity (Pearson-Fuhrhop et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, use of the galantamine-memantine combination to treat negative symptoms is an additional benefit. Finally, to treat negative symptoms in schizophrenia, medications that target the glutamatergic system and α7nACh receptors are hypothesized to yield positive results [127-129]. …”
Section: Negative Symptomsmentioning
confidence: 99%
“…This is not surprising, however, since previous studies have suggested that negative symptoms do not represent a single homogeneous symptom, but perhaps multiple psychopathological constructs influenced by a variety of systems and genetic variants. 60 This suggests that what manifests as behaviourally similar negative symptoms may be caused by abnormalities in disparate underlying pathways.…”
Section: Limitationsmentioning
confidence: 99%